Analysis of Small and Medium Enterprises’ Crisis Management: A Multi-case Study - Pradeep Kumar Aggarwal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Crisis management work includes a range of viewpoints from recession effects, strategic perspective and direction, risk managing & professional skills. Something that isn't so obvious is how small to medium-level companies function through dynamic crisis response systems. There exists very little knowledge regarding the way in which SMEs organize, react, restore & develop via crisis situations. To address this gap in the research, a multi-case research seeks to examine the real disaster management strategies of 5 SMEs. The present research aims to discuss the processes associated with SMEs that are utilized to handle crises. The case study findings indicate that SMEs demonstrate robust business sensitivity given their capital limitations and fairly poor market positions. Furthermore, this paper indicates that successful SME crisis management requires strategic market strategy for balanced development & resolution.